Strategi peningkatan usaha pemasaran ikan hasil budidaya keramba jaring apung masyarakat Desa Kampung Panjang - Hayatul Ismi; Hasby Abiyyu Farras; Tanaya Annisa Putri; Ainul Mardiah; Theresia Evelina; Ranti Oktaviana; Roulina Matanari; Helfi Safrita; Allya Eka Nursanty; Yoga Saputra; Samuel Pakpahan (Unri Conference Series: Community Engagement, 2022)
This research focuses on strategies to increase the marketing efforts of fish from the cultivation of floating net cages through the use of social media "Facebook" as a medium to promote fish production in floating net cages in Kampung Panjang Village, North Kampar District. The purpose of this study is to increase the potential of Kampung Panjang Village through marketing fish farming products on the Floating Net Cage (KJA) by providing knowledge and practice to Village-Owned Enterprises (BUMDes) so that they are able to reach as many customers as possible effectively and efficiently. The method used is a discussion and practice method consisting of two stages, namely the preparation stage and the implementation stage of activities. The results of the research are expected that business actors will be able to be skilled in marketing fish from the cultivation of floating net cages in Kampung Panjang Village through the use of "Facebook" and get convenience in the marketing process and can continue to develop their business in the midst of intense competition in the current digitalization era.